2017
DOI: 10.1089/ars.2017.7006
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-Enhanced Ultrasound for Assessing Renal Perfusion Impairment and Predicting Acute Kidney Injury to Chronic Kidney Disease Progression

Abstract: These results indicate that CEUS enables the evaluation of renal perfusion impairment associated with CKD after ischemic AKI and may serve as a noninvasive technique for assessing AKI-CKD progression. Antioxid. Redox Signal. 27, 1397-1411.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 47 publications
4
38
0
Order By: Relevance
“…The significant reduction in the refilling of the vessels is most likely due to compression, caused by the interstitial edema and accumulated red blood cells. Even though MBs returned to the renal vascular bed after 60 min of reperfusion, the MB velocity and perfusion index were lower compared with baseline; this is also in accordance with previous studies [8]- [10] and with our power Doppler scans. Despite the differences in reperfusion immediately after clamp release and the differences between the H&E stains, a direct distinction between the 60 min SRI scans of the two rats could not be made.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The significant reduction in the refilling of the vessels is most likely due to compression, caused by the interstitial edema and accumulated red blood cells. Even though MBs returned to the renal vascular bed after 60 min of reperfusion, the MB velocity and perfusion index were lower compared with baseline; this is also in accordance with previous studies [8]- [10] and with our power Doppler scans. Despite the differences in reperfusion immediately after clamp release and the differences between the H&E stains, a direct distinction between the 60 min SRI scans of the two rats could not be made.…”
Section: Discussionsupporting
confidence: 93%
“…The renal vein clamp causes the severest tissue damage [7]. Is has been shown that the blood flow in the kidneys is reduced after ischemia with subsequent reperfusion [8]- [10].…”
Section: Introductionmentioning
confidence: 99%
“…Because the reproducibility of RT was poor, and the sensitivity and specificity of medullary AUC were low, based on their consistent reliability, we suggest MTT and WIS at the renal cortex and PI at the renal medulla for diagnosing the severity and predicting the renal prognosis in patients with AKI. Previous studies have shown that renal microcirculatory perfusion is impaired in animal models of AKI [12][13][14], and in humans with septic shock [15]. One animal study showed that perfusion impairment correlated with renal histological injury and CKD progression [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that renal microcirculatory perfusion is impaired in animal models of AKI [12][13][14], and in humans with septic shock [15]. One animal study showed that perfusion impairment correlated with renal histological injury and CKD progression [14]. However, previous literature lacked any assessment of the association between CEUS-driven parameters and the clinical outcomes of human AKI, which is vital for the validity of CEUS for use in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to be a cost-effective modality for evaluating renal function impairment (RFI) [6]. Studies have shown that contrast-enhanced US is almost as sensitive as radioisotope renography in the quantitative diagnosis of chronic renal insufficiency, and correspondingly, contrast-enhanced US could be a useful tool for the assessment of renal function in children with UPJO [7][8][9]. Ionizing radiation exposure is a known risk factor for patients with leukaemia and brain tumours, especially for children with a higher radiation sensitivity and longer life expectancy [10,11].The European Federation of Societies for Ultrasound in Medicine and Biology( EFSUMB)release guidelines state that intravenous CEUS is safe and effective in paediatric populations and can be used effectively to avoid ionizing radiation exposure [11].…”
Section: Introductionmentioning
confidence: 99%